Antropologia della logistica urbana. Turismo, infrastrutture e località a Exarchia, Atene - Della Puppa, Anna Giulia (Antropologia Pubblica, 2025)
This paper focuses on the transformative impacts of tourism mobility on urban spaces, with a particular focus on the role of infrastructures as tools of power and control. Through an ethnographic exploration of Exarchia, Athens, we investigate how the construction of Metro Line 4 station, as a key infrastructure project, entangles with gentrification processes and spatial inequalities. Infrastructures, as socio-material assemblages, are deeply embedded within broader social, political, and cultural contexts, shaping patterns of inclusion and exclusion. The influx of mass tourism and its overburdening of existing infrastructures, results in spatial transformations that privilege specific modes of mobility and consumption. The case of Exarchia highlights how infrastructures are implicated in processes of social control, inequality, but also resistance. By adopting an ethnographic approach, we delve into the complex relationships between people, places, and things, and underscore the temporal dimension of infrastructures in shaping urban imaginaries and experiences. The paper emphasizes the Metro Line 4 station as a potential tool for gentrification, analyzing how its development may contribute to reinforce existing power structures and create new forms of marginalization. However, it also acknowledges the potential for counter-use and resistance within these infrastructures. By reframing infrastructures as political elements of the urban landscape, it becomes possible to envision spaces for genuine and non-rhetorical participation in urban planning, where infrastructures can serve as a true infrastructure of care.